The impact of the provincial minimum wage on environmental quality in indonesia - Ahadiyah, Siti Aminatul; Setyadharma, Andryan (Universitas Muhammadiyah Yogyakarta, 2023)
This research aims to determine the relationship between provincial minimum wages, poverty, unemployment, and income inequality to the environmental quality index (EQI). This research also aims to demonstrate if the Environmental Kuznet Curve (EKC) hypothesis is applicable in Indonesia. This research utilized secondary data collected from 33 provinces in Indonesia between 2012 and 2021. This research used panel regression with Fixed Effect Model (FEM) as the research method. The research results indicated that the provincial minimum wages and poverty positively and significantly affected the EQI. The results also demonstrated that the EKC hypothesis holds true in Indonesia, as illustrated by the significance of the GRDP per capita and GRDP per capita squared. Meanwhile, this research showed that unemployment and income inequality did not significantly impact the environmental quality index. This study offered a new analysis on the impact of provincial minimum wage on EQI in Indonesia. Therefore, this study has contributed to the additional information to the body of knowledge. The government needs to strive for an increase in the development and use of environmentally friendly products, as well as optimization of environmental protection programs. In addition, government needs to increase the provincial minimum wage according to limits set to improve environmental quality. The limited variables and research methods used are expected that further research can complement this study.